Розробка дизайну корпоративного сайту IT-студії з розробки web-сайтів «popeye solutions» - Нагорняк, А. І. (ХНУРЕ, 2025)
In today's digital world, a corporate website is an essential tool for IT companies specializing in web development. The main goal of this project is to create a modern, functional, and visually appealing website design for 'Popeye Solutions'. This thesis explores the key stages of the design development process, including research, UI/UX design principles, prototyping, and final implementation.
Keywords: корпоративний сайт; IT-студія